2016
DOI: 10.1159/000454767
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict the Presence and Severity of Intra-Abdominal Adhesions before Cesarean Delivery

Abstract: Aims: The study aimed to investigate whether we can predict the presence and severity of intra-abdominal adhesions before cesarean delivery using patient history, symptoms, and abdominal skin scar characteristics. Methods: In this prospective study, 143 pregnant women with history of previous abdominal surgery were included and they delivered by cesarean. Preoperative abdominal scar characteristics and symptoms as well as intraoperative abdominal adhesions were evaluated using the Manchester Scar Scale, a symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…In a systemic review of 29 trials published by Bamigboye et al [18] limited and inconsistent evidence was found regarding the relationship between adhesion formation and closure versus non-closure, while the non-closure technique was associated with shorter surgical time [18] Neither of the demographic factors in this study was found to be associated with the severity of adhesions. This is similar to the results found by Taylan et al [2] Stocker et al [11] and Çim et al [19]. The current study attempted to apply two skin markers together, each of which had previously been taken by other researchers as separate factors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a systemic review of 29 trials published by Bamigboye et al [18] limited and inconsistent evidence was found regarding the relationship between adhesion formation and closure versus non-closure, while the non-closure technique was associated with shorter surgical time [18] Neither of the demographic factors in this study was found to be associated with the severity of adhesions. This is similar to the results found by Taylan et al [2] Stocker et al [11] and Çim et al [19]. The current study attempted to apply two skin markers together, each of which had previously been taken by other researchers as separate factors.…”
Section: Discussionsupporting
confidence: 86%
“…Cesarean section (CS) is one of the most common operations done in the obstetric ward, and its usage is rapidly rising [1]. In the United States, the rate of Cesarean delivery during the last twenty-five years has risen to 30% of all deliveries; and in the last ten years, it has become the fifth-most-frequent surgical procedure performed in the U.S [2]. According to the annual statistical report published by the Iraqi Ministry of Health in 2017, the rate of Cesarean section deliveries in Iraq was 33.2% [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Taylan et al evaluated the skin scar characteristics of pregnant women with any kind of previous abdominal surgery at CS. 24 Although the abdominal scar score was higher in the adhesion group, no correlation was found between the scar score and the adhesion score. When compared to our results, we found a positive correlation between the subcutaneous scar tissue stiffness and intra-abdominal adhesions and subcutaneous tissue stiffness ≥36.5 had 74.4% sensitivity and 40.5% specificity for the prediction of moderate or severe adhesions.…”
Section: Discussionmentioning
confidence: 85%
“…Besides, Taylan et al . evaluated the skin scar characteristics of pregnant women with any kind of previous abdominal surgery at CS 24 . Although the abdominal scar score was higher in the adhesion group, no correlation was found between the scar score and the adhesion score.…”
Section: Discussionmentioning
confidence: 99%